On the substrate turnover rate of NBCe1 and AE1 SLC4 transporters: structure-function considerations - Pushkin, Alexander; Kao, Liyo; Zhekova, Hristina R.; Azimov, Rustam; Abuladze, Natalia; Shao, Xuesi M.; Tieleman, D. Peter; Kurtz, Ira (Frontiers in Physiology, 2025)
A transport protein’s turnover rate (TOR) is the maximum rate of substrate translocation under saturating conditions. This parameter represents the number of transporting events per transporter molecule (assuming a single transport site) per second (s). From this standpoint, a transporter’s TOR is similar to an enzyme’s catalytic constant. Knowledge of a transporter’s TOR allows comparison of the transport capacity of various transporters at the molecular level as well as the total transport per cell and whole organ levels. Despite this, there is currently a very limited number of transporters, for which TOR has been determined experimentally. In the SLC4 transporter family of CO32−/HCO3− transporters, erythrocyte AE1 (eAE1; SLC4A1) is the only member, for which TOR has been determined (∼50,000 s−1). Whether other SLC4 family members have similar TOR values is currently unknown. Here we report TOR measurements of the electrogenic Na+-CO32− cotransporter NBCe1-A (SLC4A4) and the kidney specific AE1 splice variant, kAE1, that play important roles in renal bicarbonate absorption and are mutated in proximal and distal renal tubular acidosis respectively. We have also remeasured the eAE1 TOR value for comparison. NBCe1-A had a TOR value of ∼30,400 s−1 whereas kAE1 and eAE1 had significantly higher values (62,000 s−1 and 60,500 s−1 respectively). We modeled the inward-facing (IF) conformation of NBCe1-A to determine conformational changes during its transport cycle. Comparison of this IF model with our previously determined cryoelectron microscopy (cryoEM) outward-facing (OF) conformation structure, demonstrates that NBCe1-A has an elevator-type transport mechanism with a small vertical ∼5 Å shift of the ion coordination site as we have previously shown for AE1. We speculate that this very small vertical movement plays an important role in contributing to the very high TOR numbers of SLC4 transporters.